Quantitative micrometer-scale heat dissipation analysis using pixel-level emissivity correction-based operando IR thermography - Seongjin Kim; Jae Yong Song (Case Studies in Thermal Engineering)
Infrared (IR) thermography is widely used for non-invasive, real-time thermal analysis of semiconductor devices. However, quantitative measurements remain challenging for heterogeneously integrated devices composed of various materials with varying IR emissivities (ranging from 0 to 1). Here, we present a practical and reliable pixel-level emissivity correction method, where the emissivity of heterogeneous materials (ranging from 0.21 to 0.97) is quantitatively calibrated by measuring radiance at known temperatures using an IR camera, in conjunction with high-emissivity reference segments. Using this operando IR thermography, we experimentally analyze the heat dissipation behavior of an NPU device consisting of 4 mm-scale cores, each comprising six submillimeter-scale sub-cores, with a spatial resolution of 2.4 μm. The results indicate that heat originating from hotspots on the NPU cores is transferred toward the edge of the device and that heat dissipation reaches a saturation over time. Despite thermal resistance between the sub-cores, heat is continuously dissipated without abrupt temperature changes. The proposed operando IR thermography is expected to have broad applicability in microscale thermal management of heterogeneously integrated devices.